Correlation Between Squamous Cell Carcinoma Antigen Level and the Clinicopathological Features of Early-Stage Cervical Squamous Cell Carcinoma and the Predictive Value of Squamous Cell Carcinoma Antigen Combined With Computed Tomography Scan for Lymph Node Metastasis. Issue 9 (1st November 2017) - Xu, Dianbo; Wang, Danbo; Wang, Shuo; Tian, Ye; Long, Zaiqiu; Ren, Xuemei
Abstract : Objective: The aim of this study was to analyze the relationship between serum squamous cell carcinoma antigen (SCC-Ag) and the clinicopathological features of cervical squamous cell carcinoma. The value of SCC-Ag and computed tomography (CT) for predicting lymph node metastasis (LNM) was evaluated. Methods: A total of 197 patients with International Federation of Gynecology and Obstetrics stages IB to IIA cervical squamous cell carcinoma who underwent radical surgery were enrolled in this study. The SCC-Ag was measured, and CT scans were used for the preoperative assessment of lymph node status. Results: Increased preoperative SCC-Ag levels were associated with International Federation of Gynecology and Obstetrics stage ( P = 0.001), tumor diameter of greater than 4 cm ( P < 0.001), lymphovascular invasion ( P = 0.001), LNM ( P < 0.001), and greater than one half stromal infiltration ( P < 0.001). Multivariate analysis identified LNM ( P < 0.001, odds ratio [OR] = 4.399), tumor diameter of greater than >4 cm ( P = 0.001, OR = 4.019), and greater than one half stromal infiltration ( P = 0.002, OR = 3.680) as independent factors affecting SCC-Ag greater than or equal to 2.35 ng/mL. In the analysis of LNM, SCC-Ag greater than or equal to 2.35 ng/mL ( P < 0.001, OR = 4.825) was an independent factor for LNM. The area under the receiver operator characteristic curve (AUC) of SCC-Ag was 0.763 for all patients, and 0.805 and 0.530 for IB1 + IIA1 and IB2 + IIA2 patients, respectively; 2.35 ng/mL was the optimum cutoff for predicting LNM. The combination of CT and SCC-Ag showed a sensitivity and specificity of 82.9% and 66% in parallel tests, and 29.8% and 93.3% in serial tests, respectively. Conclusions: The increase of SCC-Ag level in the preoperative phase means that there may be a pathological risk factor for postoperative outcomes. The SCC-Ag (≥2.35 ng/mL) may be a useful marker for predicting LNM of cervical cancer, especially in stages IB1 and IIA1, and the combination of SCC-Ag and CT may help identify patients with LNM to provide them with the most appropriate therapeutic approach.